Valley resolved dynamics of phonon bottleneck in semiconductor molybdenum ditelluride - Zhong Wang; Yijie Shi; Yu Pan; Min Li; Xi Wang; Zheng Zhang; Xiangyu Zhu; Fuyong Hua; Qian You; Chunlong Hu; Junjie He; Yu Ye; et al. (Communications Physics)
Abstract Semiconductor molybdenum ditelluride (2H-MoTe2) possess multiple valleys in the band structure, enriching its physical properties and potentials in applications. However, the effect of multiple valleys on the mechanisms of population and relaxation of carriers and phonons remains limited, particularly due to the inadequacy of current optical probes that lack momentum sensitivity. Here, we rely on time resolved measurements of optical absorption and electron diffraction to investigate the carrier intra- and intervalley scattering and the phonon dynamics in different valleys in photoexcited few-layer 2H-MoTe2. Our experimental results are complemented by density functional theory calculations and molecular dynamics simulations. We reveal the pathways and timescales of carrier relaxation, accompanied with the emissions of optical phonons at the Brillouin zone center and acoustic phonons at the zone border. We estimate the population of different phonon modes based on the measured results, identifying quantitatively the occurrences of phonon bottleneck located in different valleys. Our technique allows constructing a comprehensive picture of the complex interactions between carriers and phonons in 2H-MoTe2 with the valley degree of freedom resolved.